2021
DOI: 10.1128/msystems.00422-21
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of N ε -lysine Acetylation towards Regulation of Bacterial Pathogenesis

Abstract: N ε -lysine acetylation is an important, dynamic regulatory posttranslational modification (PTM) that is common in bacteria. Protein acetylomes have been characterized for more than 30 different species, and it is known that acetylation plays important regulatory roles in many essential biological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…S4). The accumulation of acetyl-CoA and succinyl-CoA in both phenylalanine metabolism and propanoate metabolism was related to bacterial physiology and virulence via lysine acetylation, which was a post-translational modification [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…S4). The accumulation of acetyl-CoA and succinyl-CoA in both phenylalanine metabolism and propanoate metabolism was related to bacterial physiology and virulence via lysine acetylation, which was a post-translational modification [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic pathways are essential for the continued growth and persistence of P. gingivalis in the microbial community as they produce ATP and promote the release of short fatty acids required for bacterial growth and survival [ 85 ]. Protein acetylation leads to the activation of proteases which aids pathogenesis in periodontitis through the degradation of host extracellular matrix components, degradation of antimicrobial peptides and cytokines [ 86 ]. Proteins such as Mfa1 fimbrilin, Haemagglutinin protein HagA and Methionine gamma-lyase related to P. gingivalis pigmentation were identified as targets of acetylation.…”
Section: Post-translational Mechanisms Of Pathogenicity In Periodonta...mentioning
confidence: 99%
“…However, recent research has found that bacterial-derived effectors can directly modify host proteins PTMs. While some pathogens have acquired and incorporated host enzymes into their virulence factor repertoire, others have convergently evolved to mimic the activity of host enzymes (Bernal et al, 2014; Luu and Carabetta, 2021; Salomon and Orth, 2013). Importantly, bacterial effectors that are translocated and directly bind host proteins to differentially acetylate them remain to be identified.…”
Section: Mainmentioning
confidence: 99%